Struktur Modal, Efisiensi Intermediasi, dan Profitabilitas Bank: Evidensi Perusahaan Tercatat di Bursa Efek Indonesia - Andi Nurhaeda; Andi Rudy Arfah (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Banking is a key pillar of the financial system, playing a crucial role as an intermediary between those with excess funds and those in need of financing. In the context of post-pandemic economic recovery in the 2022–2024 period, bank sustainability and resilience, particularly in terms of profit-generating ability, are crucial aspects to consider. This study was conducted to analyze the extent to which capital structure and intermediation efficiency influence the profitability of banks listed on the Indonesia Stock Exchange. Capital structure in this study is proxied by the Capital Adequacy Ratio (CAR), while intermediation efficiency is measured by the Loan to Deposit Ratio (LDR). The profitability indicator used is Return on Assets (ROA), which reflects a bank's effectiveness in utilizing its assets to generate profits. This research methodology uses a quantitative approach through multiple linear regression analysis with secondary data in the form of annual financial reports from 111 banks for the 2022–2024 period. The analysis results show that simultaneously, CAR and LDR variables have a significant effect on ROA. Furthermore, both variables have been shown to contribute positively to increasing bank profitability. In other words, maintaining adequate capital and efficient credit management can strengthen overall financial performance. This finding offers strategic implications for bank management in formulating capital and liquidity management policies. Optimizing these two aspects not only impacts short-term profit achievement but also contributes to the stability and sustainability of banking profitability in the long term. Therefore, banks need to ensure a strong capital strategy coupled with efficient intermediation to be more resilient in facing future economic dynamics.